Influence of Emerging Technologies on Digital Innovation and Change Management Among Private Universities Administrative Staff in Ekiti State, Nigeria - Ayo-Ogunlusi, Veronica Abiola; Obi, Sabina Nwakaego (STKIP Pesisir Selatan, 2025)
The rapid evolution of emerging technologies has transformed administrative operations in higher education, yet their effective integration in Nigerian private universities remains inconsistent. Many institutions continue to rely on traditional, paper-based processes, leading to inefficiencies, data inaccuracy, and limited organisational innovation. This study examined the influence of emerging technologies on digital innovation and change management among private universities administrative staff in Ekiti State, Nigeria. A quantitative cross-sectional survey design was adopted to collect data from the entire population of 108 administrative staff across three private universities—Afe Babalola University, Hillside University, and Venite University. Using a structured questionnaire validated by experts and tested for reliability (Cronbach’s α = 0.86), data from 102 valid responses were analysed with descriptive and inferential statistics, including multiple regression analysis at a 0.05 significance level. Findings revealed a high level of adoption of emerging technologies, with strong positive and statistically significant relationships between technology use, digital innovation (R² = 0.452), and change management (R² = 0.420). The combined effect (R² = 0.520, p < 0.05) confirmed that emerging technologies substantially enhance administrative innovation and adaptability to organisational change. The study concludes that the integration of digital tools promotes efficiency, creativity, and responsiveness in university administration. It recommends continuous staff capacity building, investment in ICT infrastructure, and strategic leadership engagement to sustain technological transformation. The study contributes empirical evidence to the discourse on digital governance and organisational change, offering practical insights for higher education administrators and policymakers.